New beaded lacewings (Neuroptera: Berothidae) from Upper Cretaceous Myanmar amber. (31st December 2016) - Yuan, Dandan; Ren, Dong; Wang, Yongjie
Abstract: Two new genera with two new species in Berothidae, Maculaberotha nervosa gen. et sp. nov. and Magniberotha recurrens gen. et sp. nov., are described from Upper Cretaceous Myanmar (Burmese) amber. Based on the new specimens of the same species, we propose some venational characters as intraspecific variations, e.g., the markings on the wings and crossveins in the radial sector. We also study and compare the female genital sclerites from three genera of Haploberotha, Dasyberotha, and Jersiberotha to highlight the importance of using these characters preserved in amber for taxonomic and phylogenetic studies. Furthermore, an updated key to the berothid genera of Myanmar amber is provided.